A mediation model of the relationship between university students’ news media literacy and xenophobia: The role of intellectual humility, perceived threat, and blind patriotism - Lin, Muyingnan; Chai, Ching Sing; Liang, Jyh-Chong (Frontiers in Psychology, 2022)
The dissemination of misinformation and disinformation has increased the need for news media literacy. This study administered a self-developed questionnaire to measure the relationship between news media literacy and xenophobia among college students in China (N = 430). The questionnaire measured five variables: news media literacy, xenophobia, blind patriotism, perceived threat, and intellectual humility. Confirmatory factor analysis was used to validate this five-variable survey, and the analyses indicated satisfactory construct validity. Results from structural equation modelling indicated that intellectual humility was a significant predictor of news media literacy, and blind patriotism and perceived threat mediated the relationship between news media literacy and xenophobia. This study provides insights for researchers and instructors who are promoting news media literacy education in schools.